Unheil durch Dämonen? Geschichten und Diskurse über das Wirken der Ginn. Eine sozialanthropologische Spurensuche in Syrien - Fartacek, Gebhard (2010)
Narratives about people haunted by demons have a long tradition in the Middle East. The Koran addresses the existence of demons, although their overall significance in it is limited. In contrast, dangerous demons and accompanying phenomena, such as the evil eye and witchcraft, play a vital role in concepts of folk religion. Particularly in peripheral and rural areas of the present-day Syrian Arab Republic, many people have stories to tell about their own encounters with such supernatural beings. In my research, I have collected such narratives, orally transmitted over time, and I have reconstructed subsequent discourses. More specifically, I have pursued the two following questions: In which spatial and temporal spheres do demons appear? And: Which human behaviours are likely to cause dangerous demons to appear? My analysis firstly replicated and extended structural approaches which presume demons and other metaphysical entities in spatial and temporal border zones. Secondly, evidence was collected to demonstrate that demons appear primarily when humans are faced with uncertainties - regarding ethical-moral decisions, regarding the realm of sexuality, or the construction of individual and collective identities. Narratives about encounters with demons inevitably lead to discourses about important issues of great urgency. In theory they can be described as conflict-laden topics regarding ethics and morals, sexuality, social change, and identity. However, the topics of these discourses are not abstract theories claiming universal validity. Quite the contrary: On the basis of concrete events in concrete contexts, concrete options for a virtuous and good life are discussed. These concretizations, in the narratives as well as in the discourses, form an effective strategy in creating security in a world full of uncertainties. The folk religious concepts regarding the demons' influence therefore provide an opportunity to cope with negative experiences of contingency. Moreover, particular relevance of the local-cultural beliefs in demons lies in dealing with value conflicts. Focusing on situations of daily life, such local-cultural concepts appear to be valid even when contrasted with other, concurring models of reality. Viewed in this light, they are essential, practical, and useful for the people in the Syrian periphery - at least today, and perhaps also tomorrow.